ANALISIS PERKEMBANGAN MOTORIK KASAR MELALUI GERAKAN TARI DOLALAK PADA SISWA KELAS V SD NEGERI PURWOREJO - Nur Laela; Arum Ratnaningsih; Rintis Rizkia Pangestika (STKIP Subang, 2024)
The aim of the research is to analyze how students' gross motor skills develop through the dolalak dance movements of class V students at Purworejo State Elementary School. In accordance with the objectives of the research conducted, this research uses qualitative descriptive research. Qualitative research method is research based on a postpotivism philosophy which is used to examine the condition of scientific objects, where the researcher is the key instrument. The data collection technique is carried out by triangulation (a combination of observation, interviews, documentation), and the data to be obtained is qualitative data, the results of qualitative research are to understand meaning, understand uniqueness, and also to find hypotheses. The results obtained from involvement in dolalak dancing activities are that students can perform longer work, use energy more economically, and study longer than untrained students. Dancing education needs to be preserved so that it can preserve culture and make students live healthy lives. Gross motor processes are only found during dolalak dancing and also during gymnastics, because in the classroom there are no other gross motor processes. During dolalak dance creation exercises, students are more interested in moving and following the movements exemplified by the teacher so that the child's gross motor development develops well.